1924
DOI: 10.1001/jama.1924.02650290030008
|View full text |Cite
|
Sign up to set email alerts
|

Antacids in the Medical Management of Peptic Ulcer

Abstract: the median number of rubs. This, however, is easily explained. It means merely that the more susceptible patients develop mercurialism, not only after a smaller number of rubs, but of a type that progresses in sever¬ ity much more rapidly than with the less susceptible patients.The* results of all the series show that the average susceptibility is strikingly uniform in different series, if a sufficient number of patients is observed. They show also, however, that the susceptibility of a consid¬ erable number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1924
1924
1942
1942

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…These findings were confirmed by Shattuck, Rohdenburg and Booher. 3 Gatewood and his co-workers,4 however, in a series of forty-six patients with peptic ulcer treated by the Sippy method, found that there was no definite evidence that the alkalemia observed was productive of any renal change. Definite nephritis was not recognized in any patients in whom alkalosis later developed.…”
Section: Abstract Of Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These findings were confirmed by Shattuck, Rohdenburg and Booher. 3 Gatewood and his co-workers,4 however, in a series of forty-six patients with peptic ulcer treated by the Sippy method, found that there was no definite evidence that the alkalemia observed was productive of any renal change. Definite nephritis was not recognized in any patients in whom alkalosis later developed.…”
Section: Abstract Of Discussionmentioning
confidence: 96%
“…In about 50 per cent of the animals thus operated on, peptic ulcer developed in the duodenal mucosa at the usual site for the development of duodenal ulcer in man. 3 Finally, the entire normal mechanism for receiving the acid gastric contents was eliminated by the func¬ tional resection of the duodenum together with the secretion poured into it. This was accomplished in the following manner : The pylorus was sectioned and the distal end inverted; the jejunum was transected a few centimeters distal to the ligament of Treitz ; the distal end was anastomosed to the pylorus, and the proximal end was anastomosed to the ileum from 30 to 60 cm.…”
Section: Methods Of Producing Ulcermentioning
confidence: 99%
See 1 more Smart Citation
“…40 Citrates have been used in very small doses in the treatment for peptic ulcer.41 Both acid and basic chlorides are lost in aspirations and vomiting. 40 Citrates have been used in very small doses in the treatment for peptic ulcer.41 Both acid and basic chlorides are lost in aspirations and vomiting.…”
Section: Report Of Casesmentioning
confidence: 99%